A psychobiography of John F. Kennedy, Jr. : understanding his inner life, achievements, struggles, and courage - Ponterotto, Joseph G. (Springfield, Illinois : Charles C. Thomas, Publisher, 2018)
This book represents a psychobiographical story of John F. Kennedy, Jr. It covers JFK Jr.'s search for identity and purpose, and the depths and vibrancy of his personality. The author approaches the life of JFK, Jr. as a psychologist and psychobiographer with the goal of understanding the workings of John's mind; his inner feelings, fears, hopes, and desires perhaps not visible on the surface. This book will be an insightful resource to address unanswered questions about JFK Jr.'s life and potential future had he lived a full life.
Chapter Six EMERGING ADULTHOOD: LAW YEARS AND CAREER EXPLORATIONSUMMARY: REFLECTIONS OF JOHN F. KENNEDY JR.'S ONGOING PERSONALITY DEVELOPMENT IN EMERGING ADULTHOOD; Chapter Seven EARLY ADULTHOOD: RELATIONSHIP COMMITMENT AND SEARCH FOR CAREER NICHE; Contemplating Marriage to Carolyn; SUMMARY: REFLECTIONS ON JOHN F. KENNEDY, JR.'S PERSONALITY DEVELOPMENT IN EARLY ADULTHOOD; Part Three WHAT COULD HAVE BEEN IN THE LIFE OF JOHN F. KENNEDY, JR., AND CAROLYN BESSETTE KENNEDY?; Chapter Eight POSSIBLE PATHS FOR JFK JR.'S CAREER AND FAMILY; Challenges in Marriage
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Kennedy, John F., -- Jr., -- 1960-1999 -- Psychology; Kennedy, John F., -- Jr., -- 1960-1999.; Children of presidents -- United States -- Biography; Children of presidents; Psychology; United States; BIOGRAPHY & AUTOBIOGRAPHY / Historical; HISTORY / United States / State & Local / General; Biography; Electronic books